2020
DOI: 10.3390/biom10020271
|View full text |Cite
|
Sign up to set email alerts
|

Electrophiles against (Skin) Diseases: More Than Nrf2

Abstract: The skin represents an indispensable barrier between the organism and the environment and is the first line of defense against exogenous insults. The transcription factor NRF2 is a central regulator of cytoprotection and stress resistance. NRF2 is activated in response to oxidative stress by reactive oxygen species (ROS) and electrophiles. These electrophiles oxidize specific cysteine residues of the NRF2 inhibitor KEAP1, leading to KEAP1 inactivation and, subsequently, NRF2 activation. As oxidative stress is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 153 publications
(258 reference statements)
0
21
0
Order By: Relevance
“…This discrepancy enhances the importance of the results presented in the current study, showing that phytonutrient combinations caused, in some cases, four to five times higher inhibition of IL-6 secretion and activation of ARE/Nrf2 activity than the activity of the single compounds. The ARE/Nrf2 mediated protection is probably due to a reduction in oxidative stress [ 33 , 37 ], and also because the ARE/Nrf2 pathway inhibits NFκB-mediated transcription [ 38 , 39 , 40 ] (see Scheme 1 ). This may occur by several mechanisms, e.g., one of the target proteins of Nrf2, heme oxygenase 1, binds to nuclear NFκB p65 and inhibits its activity [ 41 ], and Kelch-like ECH-associated protein 1 (KEAP1) which is the negative regulator of Nrf2, can interact with IκB kinase β (IKKβ), which is a positive regulator of NFκB.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy enhances the importance of the results presented in the current study, showing that phytonutrient combinations caused, in some cases, four to five times higher inhibition of IL-6 secretion and activation of ARE/Nrf2 activity than the activity of the single compounds. The ARE/Nrf2 mediated protection is probably due to a reduction in oxidative stress [ 33 , 37 ], and also because the ARE/Nrf2 pathway inhibits NFκB-mediated transcription [ 38 , 39 , 40 ] (see Scheme 1 ). This may occur by several mechanisms, e.g., one of the target proteins of Nrf2, heme oxygenase 1, binds to nuclear NFκB p65 and inhibits its activity [ 41 ], and Kelch-like ECH-associated protein 1 (KEAP1) which is the negative regulator of Nrf2, can interact with IκB kinase β (IKKβ), which is a positive regulator of NFκB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore dimethyl fumarate (DMF), which activates Nrf2, is already used clinically to treat inflammatory diseases. DMF was approved for the treatment of patients with moderate and severe psoriasis as well as patients with relapsing remitting multiple sclerosis (65). In addition, there are clinical trials ongoing with DMF for treatment of inflammatory conditions, among others cutaneous lupus erythematosus (66).…”
Section: Discussionmentioning
confidence: 99%
“…This transcription factor is generally activated in response to ROS production and oxidative stress, inducing the downstream expression of antioxidative and phase II detoxification enzymes within the antioxidant response elements (ARE) such as heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase 1 (NQO1), glutathione S-transferase, CAT and SOD (Wang et al, 2018a;Helou et al, 2019). The role of oxidative stress and Nrf2 has been extensively implicated with the pathogenesis of skin inflammation and carcinogenesis (Bickers and Athar 2006;Helou et al, 2019;Hennig et al, 2020). Early studies by Braun et al (2002) identified Nrf2 to be crucial in modulating inflammation in wound healing where persistent and prolonged inflammation associated with IL-1β, IL-6 and TNF-α was observed in Nrf2-knockout mice.…”
Section: Nuclear Factor Erythroid 2-related Factor 2 As a Target Of Xmentioning
confidence: 99%
“…Early studies by Braun et al (2002) identified Nrf2 to be crucial in modulating inflammation in wound healing where persistent and prolonged inflammation associated with IL-1β, IL-6 and TNF-α was observed in Nrf2-knockout mice. Other studies highlighted the anti-inflammatory role of Nrf2 signaling in reducing the levels of IL-1β and IL-6 to alleviate skin inflammation (Saw et al, 2010) besides suppressing the activation of inflammatory NF-κB and NLRP3 pathways (Bulugonda et al, 2017;Helou et al, 2019;Hennig et al, 2020). The Nrf2 signaling pathway was also associated with chemopreventive effects by exerting photoprotection against UVB-induced skin carcinogenesis besides protecting against inflammatory damage on the extracellular matrix (Saw et al, 2010;Saw et al, 2014).…”
Section: Nuclear Factor Erythroid 2-related Factor 2 As a Target Of Xmentioning
confidence: 99%